“Necesidades Educativas Especiales Transitorias para el aprendizaje de las Ciencias Naturales en los estudiantes de décimo año paralelo “H” de Educación General Básica, Unidad Educativa Isabel de Godín período septiembre 2016 – febrero 2017” - Veloz Bonifaz, Samantha Aracelly (2017)
This investigation is set out to explain if the Transitional Special Educational Needs influences the teaching of Natural Science learning in the Tenth Year of Basic Education room “H” from Isabel de Godín Educational Unit where it was detected that the educatoaimed at explaining if the Transitional Special Educational Needs influence the teaching of the Natural Sciences in the students of the Tenth Year of Parallel Basic Education "H" of the Educational Unit Isabel de Godín where it was detected that educators ocassionally use the methodological strategies for optimal student´s learning. To change this attitude Jerome Bruner considers of interest the development of mental abilities. It points to a theory of prescriptive instruction because it proposes rules for acquiring knowledge, skills and at the same time provides techniques for measuring and evaluating results. This theory of instruction must be concerned with a learning and development and more must be interested in what is to teach so that it learns better with a learning that is not limited to descriptive. The methodology of the work is base don document type and field design, its leve lis diagnoostic and descriptive. Fort he collection of the information used the technique of the survey with its instrument the questionnaire, applied the simple a four educators, also was applied the technique of observation with its instrument the checlist for which allowed the processing of the data. As a conclusión it can be stated that teachers are mostly unaware of the inclusión and the appropriate procedure to be given to students with the NEET, therefore, it is recommended to apply methodological strategies and activities with curricular adaptations addressing their needs.